The Balanced Scorecard Method as an Implementation of Company Performance Evaluation - Firmaniansyah, Shafa' Sania; Rofiaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – Company mergers have become a crucial strategy to enhance corporate performance, especially for state-owned enterprises (SOEs) in facing global competition. This study aims to evaluate the performance changes of PT. Alur Pelayaran Barat Surabaya (APBS) two years post-merger using the balanced scorecard approach. Design/methodology/approach – The study employs a qualitative method with data collection techniques including documentation, questionnaires, and interviews. Key informants consist of the CEO and directors in the fields of commercial, operations, engineering, human resources, general affairs, and finance, supported by two additional informants. Findings – The results indicate that, from a financial perspective, the company's performance is considered excellent based on ROE, NPM, and ROA indicators. From the customer perspective, the evaluation of business model innovation, operational, and CSR performance is categorized as good. In the internal business process perspective, the number of transactions increased, and the innovation interest index is also categorized as good. However, in the growth and learning perspective, employee training has not met the standards, although employee productivity and satisfaction are considered good. These findings imply the need for improvement in employee training programs to support long-term growth while maintaining and enhancing performance in other aspects. Originality/value – This research contributes originality by applying the balanced scorecard framework to assess post-merger performance in a state-owned shipping company context, which is rarely examined in existing literature. The findings offer practical value by highlighting specific strengths and weaknesses across financial, customer, internal process, and learning perspectives to support strategic decision-making.